2017
DOI: 10.3390/ijerph14070742
|View full text |Cite
|
Sign up to set email alerts
|

Health Impact of PM10, PM2.5 and Black Carbon Exposure Due to Different Source Sectors in Stockholm, Gothenburg and Umea, Sweden

Abstract: The most important anthropogenic sources of primary particulate matter (PM) in ambient air in Europe are exhaust and non-exhaust emissions from road traffic and combustion of solid biomass. There is convincing evidence that PM, almost regardless of source, has detrimental health effects. An important issue in health impact assessments is what metric, indicator and exposure-response function to use for different types of PM. The aim of this study is to describe sectorial contributions to PM exposure and related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
155
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 134 publications
(165 citation statements)
references
References 56 publications
8
155
1
1
Order By: Relevance
“…Regarding the health impact of air pollution, small health benefits within the general population and small health risks for active commuters (of only a few percent) due to increased cycling were found in most studies based on exposure-response functions from studies with comparisons of exposure between cities. Such exposure-response functions seem to underestimate the impact of vehicle exhaust exposure [108]. Three studies showed larger benefits for the general population, including the same benefits as associated with physical activity (50%) [50], larger than twice the benefits as associated with physical activity [40], and twice as large as the benefits associated with the introduction of a congestion tax in central Stockholm [37].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the health impact of air pollution, small health benefits within the general population and small health risks for active commuters (of only a few percent) due to increased cycling were found in most studies based on exposure-response functions from studies with comparisons of exposure between cities. Such exposure-response functions seem to underestimate the impact of vehicle exhaust exposure [108]. Three studies showed larger benefits for the general population, including the same benefits as associated with physical activity (50%) [50], larger than twice the benefits as associated with physical activity [40], and twice as large as the benefits associated with the introduction of a congestion tax in central Stockholm [37].…”
Section: Resultsmentioning
confidence: 99%
“…CC BY 4.0 License. resolution (STEAM3, Johansson et al, 2017), more details are given in the next section. The STEAM model version used for the CMAQ simulations was, however, not including VOC emissions.…”
Section: Model Set-upmentioning
confidence: 99%
“…The decreased levels of NOx and NO2 during the period 1990-2015 in Gothenburg were estimated to increase the life expectancy by up to 12 months and 6 months respectively, and the slight increased trend of O3 and PM10 have relatively little impact on life expectancy (-2 month and -1 month) (Olstrup et al, 2018). In terms of exposure to PM10 and PM2.5 from different source categories in Gothenburg, Segersson et al (2017) calculated that the largest part was due to the 200 long-range transport and the dominating local sources were road traffic and residential wood combustion, while the contribution from local shipping was small, 0.04 µg/m 3 population weighted annual mean PM2.5. The exposure of PM2.5 from shipping in other harbour cities in Sweden are lower than in Gothenburg, with 0.02 µg/m 3 in Stockholm and 0.01 µg/ m 3 in Umea (Segersson et al, 2017).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The adverse health impacts from air pollution and especially from particulate matter (PM) is a well-documented problem (e.g. Keuken et al, 2011;REVIHAAP, 2013;Mukherjee and Agrawal, 2017;Segersson et al, 2017). Furthermore, it affects crops yields (e.g.…”
Section: Introductionmentioning
confidence: 99%